2020
DOI: 10.1088/1361-6560/ab7e7c
|View full text |Cite
|
Sign up to set email alerts
|

Shortening delivery times for intensity-modulated proton therapy by reducing the number of proton spots: an experimental verification

Abstract: Delivery times of intensity-modulated proton therapy (IMPT) can be shortened by reducing the number of spots in the treatment plan, but this may affect clinical plan delivery. Here, we assess the experimental deliverability, accuracy and time reduction of spot-reduced treatment planning for a clinical case, as well as its robustness. For a single head-and-neck cancer patient, a spot-reduced plan was generated and compared with the conventional clinical plan. The number of proton spots was reduced using the ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…However, with current developments in controlled breath-hold [54], it is possible to hold the breath up to several minutes. Combined with recent investigations about decreasing delivery times [55], the delivery of the entire field in future will be possible within one breath-hold. Additionally, previous studies have also shown a high reproducibility of DIBH for NSCLC patients [32,56].…”
Section: Discussionmentioning
confidence: 99%
“…However, with current developments in controlled breath-hold [54], it is possible to hold the breath up to several minutes. Combined with recent investigations about decreasing delivery times [55], the delivery of the entire field in future will be possible within one breath-hold. Additionally, previous studies have also shown a high reproducibility of DIBH for NSCLC patients [32,56].…”
Section: Discussionmentioning
confidence: 99%
“…In order to remove low‐weighted spots and potentially increase the dose rate, the number of spots in all treatment plans was greatly reduced by applying the spot‐reduction algorithm presented by Van de Water et al. 20 …”
Section: Methodsmentioning
confidence: 99%
“…Please note that no air gap was modeled, representing a best‐case scenario for the range shifter plans in terms of spot sizes and thus of plan quality and integral dose. In order to remove low‐weighted spots and potentially increase the dose rate, the number of spots in all treatment plans was greatly reduced by applying the spot‐reduction algorithm presented by Van de Water et al 20 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy of the shoot-through beams was set to 230 MeV (see Table 1), with a corresponding spot width of 3.5 mm (one sigma, in-air at isocenter). Spot-reduced treatment planning was performed using the "pencil beam resampling" technique, 36 which was implemented as an inhouse developed extension of the open-source treatment planning toolkit "matRad." 37 It is an iterative planning approach, with each iteration consisting of addition of a relatively small sample of randomly selected candidate spots, followed by prioritized multicriteria dose optimization, and finally iterative exclusion of low-weighted spots while maintaining dosimetric plan quality.…”
Section: Shoot-through Planmentioning
confidence: 99%